ANALISIS FAKTOR-FAKTOR PENCAPAIAN KAPASITAS PRODUKSI KLINKER PADA PT. SEMEN TONASA PANGKEP - Taan, Hapsawati (Jurnal Sainstek, 2008)
The methode research done in PT. Semen Tonasa Pangkep production is kind of cement Portland. Method of this research are observation, the direct interview and documenter.This research aims to find out factors which influence the machine total production, start from raw mill machine until clinker machine, and ways to solve the problems in order to increase production result. Based on the data processing and analysis found that predicting method in which is used to predict future total production is regression linier predicting method, because it has the smallest MAPE, is: 0, 26%. To increase the capacity in appropriate with the analysis result, so there must be a shift-time, from 7 hours to 8 hours and weekdays from 5 weekdays into 6 weekdays. In the use of total of workers, if the company gets lots of demand, so it is better for the company to find subcontract-workers.